(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In recent years, India has seen an explosion in the environmentally conscious construction industry. Despite the widespread call for greener buildings to reduce their environmental impact, studies evaluating their effectiveness are quite uncommon. Therefore, the purpose of this research is to examine how well green building construction projects stick to their timelines, and to make suggestions that could boost that performance. This study reports the views of construction experts on the incorporation of sustainable construction in project administration in Jammu and Kashmir. In total, data were collected from 122 construction professionals who were randomly selected through the survey. In different categories, land, water, waste, energy, human resources and physical resources are used. The study revealed that the ideas of the success of the project if it works within the three objectives (time, cost and quality) influence construction professionals to underestimate the involvement of sustainability benefits (environmental, economic and social) in terms of the process used to measure the project’s project. success. However, most of the buildings in Jammu and Kashmir are very energy dependent, increasing energy wastage and reducing the comfort of residents. The result also showed that recycled construction materials are not fully used in buildings, and this is due to their unavailability in the industry, the unsustainable price of the product and the lack of incentives for the use of such materials. The study concludes that, the challenge facing the construction industry today is not only to complete projects on time, cost and quality, but to combine various constraints such as economic, environmental and social needs in the construction work. Finally, a set of proposals was presented with the aim of improving the effectiveness of the program. The findings of this study will provide a countermeasure which future green building construction initiatives may be evaluated.